2022
DOI: 10.1242/bio.059143
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic function of the peptidylarginine deiminase PADI4 is dispensable for normal haematopoiesis

Abstract: Peptidylarginine deiminases (PADIs) are strongly associated with the development of autoimmunity, neurodegeneration and cancer but their physiological roles are ill-defined. The nuclear deiminase PADI4 regulates pluripotency in the mammalian pre-implantation embryo but its function in tissue development is unknown. PADI4 is primarily expressed in the bone marrow, as part of a self-renewal-associated gene signature. It has been shown to regulate the proliferation of multipotent haematopoietic progenitors and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Of note function of PADI4 on HSC maintenance is controversial. 52 Therefore, gene expression modulated by Tempol may be associated with either oxidative stress modulation or with HSC exhaustion/proliferation balance. Our results are in favor of adding antioxidants such as Tempol to the culture medium to improve HSC maintenance in the context of cell/gene therapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Of note function of PADI4 on HSC maintenance is controversial. 52 Therefore, gene expression modulated by Tempol may be associated with either oxidative stress modulation or with HSC exhaustion/proliferation balance. Our results are in favor of adding antioxidants such as Tempol to the culture medium to improve HSC maintenance in the context of cell/gene therapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of PADI4 are less well understood, as are its modes of action under physiological conditions (whether through transcriptional, signalling or cell–ECM regulation). In healthy mammals, Padi4 is most highly expressed in the blood and the bone marrow, although it does not have a cell-intrinsic role in mouse haematopoiesis [ 14 , 15 ]. We previously demonstrated that PADI4 is also expressed in embryonic stem (ES) cells and mediates the establishment of pluripotency during the reprogramming of somatic cells to induced pluripotent stem (iPS) cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%